Innovation Electrically Heated Blankets of Temperature in the Premature Infants - หะยีเซะ, วนิสา; บิณอะฮมัด, ฮาบิบ; ซอและ, นุรไอดา; อาแว, พอตีเมาะ; มะเซ็ง, ฟัตฮียะห์; ยามาโก, ฟาซียะห์; หมันหลิน, มุสลีมะห์; เวาะสะ, มูนีเราะห์; เจ๊ะปูเต๊ะ, รูซีตา; ขุนนุรักษ์, วรัญญา; เจ๊ะโซ๊ะ, วารีซัน; อาแด, อฟัฟ (Princess of Naradhiwas University Journal, 2018)
The purpose of this quasi-experimental research (two-group post-test only design) was to compare an average body temperature between preterm infants who used Electrical Heating Blanket and the recorded body temperature of preterm infants who were in Newborn Intensive Care Unit (NICU) in the past. Purposive sampling was used. The sample was divided into two groups of 10 dyads: one control group and one experimental group. Preterm Infants in experimental group used an innovative Electrical Heating Blanket, which was developed by a researcher, then verified by 3 experts. Research instrument was a questionnaire consisting of the demographic data, temperature record, and satisfaction toward the innovation. Index of Item Objective Congruence (IOC) was verified by 3 experts, yielding values of more than 0.5. Reliability of the questionnaire was tested using Cronbach’s alpha coefficient yielding a value of 0.8. Data were analyzed by using descriptive statistics and Mann-Whitney U Test. The results of this study revealed that the mean score of the preterm infants’ body temperature who used the Electrical Heating Blanket was significantly higher than the recorded body temperature of the preterm infant who were in Newborn Intensive Care Unit (NICU) in the past (Z = -3.341, P<0.01). The satisfaction toward the innovation was at a good level (M = 4.27, S.D. = 0.46). The research findings suggest that the innovative Electrical Heating Blanket was effective. Nurse should use this innovation in NICU to reduce the hypothermia of preterm infants during transferring.